2001
DOI: 10.1080/01443410120065496
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Reading Intervention in Junior School

Abstract: The aim of this study was to evaluate an intervention strategy for children at risk of reading failure in their third year at school. Classes in ve UK junior schools were screened to identify children most at risk of reading failure (36 in total, mean initial age 7.6 years). Comparison children, matched overall for age and reading performance, were selected from comparable schools. The selected children were given an individually adaptive, curriculum-based, support programme with the emphasis on word building … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…One further potentially important factor was the group size. In the infant study, for comparability with the study reported by Nicolson et al (1999), groups of four children were used, whereas in the junior study, for comparability with the study reported by Fawcett et al (1999), groups of two were used. The teachers both remarked that whereas it is possible for an experienced teacher to make sure that all four children are actively involved with traditional teaching, this is more difficult with computer-based support since there is only one mouse, and consequently there can be a tendency for one child to dominate and others to withdraw.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One further potentially important factor was the group size. In the infant study, for comparability with the study reported by Nicolson et al (1999), groups of four children were used, whereas in the junior study, for comparability with the study reported by Fawcett et al (1999), groups of two were used. The teachers both remarked that whereas it is possible for an experienced teacher to make sure that all four children are actively involved with traditional teaching, this is more difficult with computer-based support since there is only one mouse, and consequently there can be a tendency for one child to dominate and others to withdraw.…”
Section: Discussionmentioning
confidence: 99%
“…For any ITA approach to work effectively, it is necessary to have a model of a good teaching system for the skill involved. In the infant and junior school interventions discussed above Fawcett et al, 1999) we adopted the IA&T scheme (Reason and Boote, 1994), which is a well-tested, theoretically sound, pragmatically based approach well-tuned to the problems of dyslexia and compatible with the ITA approach. Key aspects of the IA&T approach are described in Nicolson et al (1999), but a brief outline may be given here.…”
Section: The Interactive Assessment and Teaching (Iaandt) Reading Progrmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the data was not normally distributed, a series of nonparametric Wilcoxon tests were undertaken. In accordance with literature on literacy intervention studies (Fawcett et al 2001) two factor anovas were also conducted to investigate optimum age of following the intervention. This allows effect of scores at pre-test to be examined in relation to post-test and any interactions between group and time to be examined.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been an increase in intervention studies that have emphasized direct instruction on phonological awareness, letter-name and letter-sound knowledge, and whole-word reading (e.g., Blachman et al, 2004;Engelmann & Bruner, 1995b;Foorman et al, 1997;O'Shaughnessy & Swanson, 2000;Torgesen, Wagner, Rashotte, Alexander, & Conway, 1997). However, at the same time, there is a growing concern regarding the effectiveness of such training (e.g., Blachman, 1997;Bus & van IJzendoorn, 1999;Fawcett, Nicolson, Moss, Nicolson, & Reason, 2001;Schneider, Ennemoser, Roth, & Küspert, 1999). For example , Wagner, Torgesen, Laughon, Simmons, and Rashotte (1993) concluded that phonological processing training, by itself, provides, at best, limited improvement in reading ability.…”
Section: Introductionmentioning
confidence: 99%